Diversity management The millennial challenge in a group of organizations: who are they, what motivates them and how to retain them? - Mitta Flores, Daniel Eduardo (2019)
This article aims to analyze the strategies and policies applicable to a group of professional millennials and how they represent a challenge for organizations. The  millennial Generation has requirements and expectations of their work centers that may be different from those currently offered. It is for this reason that the human resources areas must know about these expectations in order to achieve efficient retention of talent. The challenges and changes that will be demanded by the members of each generation in the future oblige us to rethink these issues, making necessary to promote strategies and policies that make the collaborators feel identified and loyal to the organization. In this context, the knowledge of the characteristics of the personnel is essential, so the identification of the generational groups that compose them is key to be able to formulate an adequate retention plan for each organization because, according to the generational theory, each generational group has different expectations and  characteristics.